ANALYSIS OF PUBLIC TOURISM POLICIES IN THE BORDER ZONE OF MATO GROSSO, BRAZIL - de Souza Lima, Bruno; Fonseca de Arruda , Renato; Alves da Silva Neves , Sandra Mara; Aparecido da Costa, Edgar; da Silva Massavi, João Henrique; Alcântara Ferreira , Jordi (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
The study addresses municipal public policies for tourism along the Border Strip in the State of Mato Grosso with Bolivia. Its objective is to discuss the guidelines of these tourism policies in municipalities within this Border Strip, highlighting weaknesses and potential ways to enhance the promotion of tourism activities. Tourism activities and public policies in this region are investigated to identify weaknesses and potentials that may maximize the promotion of tourism. The research is justified by the need to create precise diagnostics about tourism along Brazil’s border in Mato Grosso, an area with great potential that remains underexplored. Methodologically, the investigation includes bibliographical research, the development of a map of tourist regions, the application of questionnaires via Google Forms to municipal managers, and graphical analysis of the responses obtained. The results show that the municipalities have few specific legislations related to tourism, low participation in regional and state governance structures, limited partnership networks, and almost no involvement in programs and projects from the Ministry of Tourism. The main economic activities in the region are livestock farming and commerce, leaving tourism in the background. It is concluded that there is an urgent need to strengthen public tourism policies along the border strip to better utilize local potentials and promote the sustainable development of the region.